2019
DOI: 10.1016/j.toxrep.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of prolonged chlorpyrifos exposure on locomotion and slow-and fast- twitch skeletal muscles contractility in rats

Abstract: Highlights Prolonged exposure to chlorpyrifos induced locomotor impairments. Chlorpyrifos exposure modified the characteristics of twitch contraction of mammalian skeletal muscle fibers. Structural and functional alterations are reported as adaptation of the fibers muscle to chlorpyrifos exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
4
3
0
Order By: Relevance
“…During twitch experiments, while the activation times of both EDL and SOL muscle were comparable to those reported in previous studies, the relaxation times for SOL muscle were significantly longer than previously reported (Hallal et al., 2019; Segal et al., 1986). When searching for L o by stretching the muscle, we noticed that the twitch relaxation time was noticeably prolonged at longer muscle lengths in SOL muscle while the twitch relaxation time appeared less sensitive to muscle length in EDL muscle.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…During twitch experiments, while the activation times of both EDL and SOL muscle were comparable to those reported in previous studies, the relaxation times for SOL muscle were significantly longer than previously reported (Hallal et al., 2019; Segal et al., 1986). When searching for L o by stretching the muscle, we noticed that the twitch relaxation time was noticeably prolonged at longer muscle lengths in SOL muscle while the twitch relaxation time appeared less sensitive to muscle length in EDL muscle.…”
Section: Discussionsupporting
confidence: 86%
“…The average plateau tension of EDL and SOL muscle during tetanic contraction reported in this study is ∼90 mN/mm 2 . Previous studies reported the tetanic tension of EDL and SOL muscle range from ∼30 mN/mm 2 (Hallal et al., 2019) to ∼170 mN/mm 2 (Segal et al., 1986; Spector, 1985). The reasons for these discrepancies are unclear.…”
Section: Discussionmentioning
confidence: 95%
“…After tension peaked, it decayed with a half-time of 659.4 ms (95% CI: 502.8 ms to 815.9 ms). The twitch tensions for both muscles reported here are comparable with those reported previously (Hallal et al ., 2019).…”
Section: Resultssupporting
confidence: 92%
“…After tension peaked, it decayed with a half-time of 659.4 ms (95% CI: 502.8 ms to 815.9 ms). The twitch tensions for both muscles reported here are comparable with those reported previously (Hallal et al, 2019). The hexagonal crystal lattice formed by the myosin-containing thick and actin-containing thin filaments in the sarcomere give rise to the two strongest equatorial reflections, the 1,0 and the 1,1.…”
Section: Structural Change During Fixed-end Twitch Contractionssupporting
confidence: 89%
“…☆The data article is related to the research article titled“Impacts of prolonged chlorpyrifos exposure on locomotion and slow-and fast-twitch skeletal muscles contractility in rats” [1]. …”
mentioning
confidence: 99%